India and its visual cultures community, class and gender in a symbolic landscape - Skoda, Uwe 1973-; Lettmann, Birgit (SAGE, 2018)
"India and its Visual Cultures is a comprehensive mapping and analysis of contemporary cultural artefacts and visual cultures through different approaches--iconographic, social, political, religious, etc. This volume covers various media and their histories. The authors study visual representational systems, production and consumption of media, and culturally specific understandings. Crucial questions about the usage of media in research are also addressed in the book. In the selection of the subjects and objects of enquiry there is a constant engagement with the popular and the everyday. The objects are studied with respect to their situatedness in urban space and everyday life. The five sections of the volume focus on five aspects of visual culture: camera works, folk/artistry, market signs, pictorial politics, and monumental landscapes. With attention to ethnographic detail and anthropology, each section brings an added dimension to the study of visible cultural forms"--Provided by publisher.